Relationship between Training Effectiveness and Work Performance: Mediation of Workplace Environment (Quest Journal of Management and Social Sciences, 2022)
Background: There is widespread agreement that training and performance are positively associated in the prior studies. However, there is a lack of empirical evidence to establish the mediating role of the workplace environment in the relationship between training and performance.Objectives: The purpose of the study was to examine the relationship between training effectiveness and work performance and the mediating role of the workplace environment.Methods: We used consecutive sampling to select respondents, adopting a descriptive cross-sectional research approach with a sample of 205 Nepalese commercial bank employees across five different commercial banks. To assess the role of the workplace environment in the relationship between training effectiveness and work performance, a self-administered structured questionnaire with 12 items was developed. Data were analyzed using SPSS and analysis of moment structures. The characteristics of the respondents were examined using descriptive statistics such as frequency distribution, and the link between training effectiveness and performance was measured using mean value analysis. Exploratory factor analysis was used to identify the factor structure of the measure used in the study and examine internal reliability. Confirmatory factor analysis and structural equation modeling were used to demonstrate the link between the three components, test the hypothesis, and mediation effect. Results: The findings of training related data indicated that 45.4% of the respondents perceived that training was highly influential, 60.0% were satisfied with the training provided, 43.9% of the respondents reported that their organization focus on both on and off-the-job training, 57.6% felt that training is crucial and 82.4% perceive that training has improved their performance and respondents positively perceived the relationship between training effectiveness and work performance. The exploratory factor analysis revealed that items on work performance, workplace environment, and training effectiveness have higher internal reliability. The hypothesis test results showed a positive association between training effectiveness, job performance, workplace environment, and work performance, and training effectiveness has the highest impact on work performance. Similarly, the results also depicted that the workplace environment mediates training effectiveness and work performance. Conclusion: The study concluded that the more effective the training, the better the employees’ work performance. As a result, greater emphasis requires improving the context and process of training from the employees’ perspective. The study also concluded that the workplace environment affects training effectiveness and work performance. Therefore, it is essential to note that Nepalese organizations should provide practical training and create a favorable work environment for better work performance.